Use of ICT/Web Tools in ELT in Nepal (Journal of NELTA, 2015)
Information and Communication Technology (ICT) has become the integral part of English Language Teaching (ELT) to meet the needs of the present day world. It has brought significant changes in the traditional teacher-centered lecturing methods. However, this emerging field of study has not been researched rigorously in the context of Nepal. Considering this, the research study carried out at the Department of English Education, Tribhuvan University, Kathmandu aimed to find out the commonly used ICT/Web tools in ELT and its positive impact on ELT practice. The sample size of the study consisted of 40 English teachers of private Secondary and Higher Secondary Schools of Kathmandu Valley. The informants were selected using judgmental non-random sampling from Kathmandu, Lalitpur and Bhaktapur districts in a proportionate way. A questionnaire consisting of both close-ended and open-ended questions was used as a data collection tool. The data were analyzed and interpreted descriptively and statistically. The result of the data obtained revealed that the ICT tools such as mobile phone, laptop, multimedia projector and web tools like YouTube, Facebook, wiki, email, blog are used in ELT and have positive impact on ELT.DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12076 Journal of NELTA, Vol 19 No. 1-2, December 2014: 1-16